Success of Local Fistula Mentorship; Review of Routine Repairs At Referral Hospital in Uganda - Namala, Angela (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess surgical capacity building training during fistula camps using FIGO competency manualand skills tracker. Methods: Between January 2016 to September 2018, six fistula camps were conducted in which the trainee worked with three expert surgeons. The trainee observed, assisted and operated fistula cases with supervision and mentorship from the FIGO accredited expert surgeons. The trainee competence was progressively monitored. Continuous mentorship and coaching was done over two years and the trainee was encouraged to do routine repairs after their skill level improved from standard to advanced level. The routine fistula repairs were done using FIGO competency manual and skills tracker by the trainee. Results: During the period, 632 patients sought care for treatment of fistula, 31% (199) were diagnosed with fistula, 92 %( 183) treated, 23%(34) through routine while 77 % (149) through camps.Out of the routine repairs, 74% (25) were simple fistulae and 26% (9) were complex 97%. Of the routine repair (33 cases) were continent at discharge with a negative dye test, while 3 %(1) had a failed repair. Conclusion: The local onsite fistula-training program is a cheaper yet successful way of capacity building for surgeons as individuals and for institutions for routine fistula repairs.